Morphine-Sparing Effect of Intermittent Versus Continuous Intravenous Infusion of Nefopam in Patients After Total Knee Arthroplasty: A Randomized Trial - Kachacheewa, Woratanat; Wattanavijitkul, Thitima; Wongsak, Siwadol; Chalacheewa, Theerawat (Ramathibodi Medical Journal, 2024)
Background: Nefopam, a nonopioid analgesic, is recommended to improve pain control and minimize opioid-related side effects following total knee arthroplasty (TKA). Objective: To compare cumulative morphine consumption between intermittent infusion (II) and continuous infusion (CI) of nefopam, combined with other multimodal analgesics, in TKA patients. Methods: Fifty-eight patients were randomly assigned to receive either intermittent nefopam infusion (II group) (20 mg IV every 6 hours) or continuous infusion (CI group) (80 mg/day). The primary outcome was cumulative morphine consumption via patient-controlled analgesia, with secondary outcomes including pain scores every 4 hours and adverse drug reactions (ADRs). Results: No significant difference was found in cumulative morphine consumption (median [range], 4 [0 -12] mg in II and 6 [0 - 18] mg in CI; P = .579) and the ADRs over 48 hours between groups. At 4 hours, the II group had significantly lower pain scores compared to the CI group (median [range], 0 [0 - 4] and 0 [0 - 8]; P = .008). However, by 24 and 36 hours, the CI group reported significantly lower pain scores compared to the II group; median (range), 0 (0 - 5) vs 2 (0 - 9) at 24 hours (P = .020) and 0 (0 - 4) vs 2 (0 - 8) at 36 hours (P = .014). Conclusions: Both intermittent and continuous nefopam infusion in primary TKA showed no significant difference in morphine-sparing or occurrence of ADRs within the 48-hour follow-up period. These findings suggest that both infusion methods are comparable in managing post-operative pain in TKA patients.